ABOUT THE EDUCATION AT THE MODERN UNIVERSITY: THE CHANGE OF THE RULES OF THE ACTING - Mikhail A. Gusakovsky (Высшее образование в России)
This article deals with a critical analysis of two types of discourse: the selfH determination personal discourse and the Care of the self discourse. The paper examines the main meaning of the Care of the Self discourse and its main components as they are presented in M. Foucault philosophy. The earliest strategy of educational practices in modern university producing by the Care of the self discourse is offered.